Dynamics of Civil Structures, Volume 4 Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014 - Catbas, Fikret Necati; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This critical collection examines a range of the dynamics of civil structures, from dynamic testing of civil structures to bridge structures to operational modal analysis, as presented in early findings and case studies from the Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014. The collection includes papers in the following general technical research areas:   ·         Modal Parameter Identification ·         Dynamic Testing of Civil Structures ·         Human Induced Vibrations of Civil Structures ·         Correlation & Updating ·         Operational Modal Analysis ·         Damage Detection of Structures ·         Bridge Structures ·         Damage Detection Models ·         Experimental Techniques for Civil Structures.
Automatic Modal Identification Based on Narrow-band Algorithms -- Cable Parameters for Homogenous Cable-Beam Models for Space Structures -- Numerical Continuation Methods for the Concept of Non-linear Normal Modes -- Strategies for Coupled Vibration Suppression and Energy Harvesting -- Expansion of Mode Shapes and Responses on the Offshore Platform Valdemar -- Vibration Testing of a Floor During Multiple Phases of Construction -- Investigation of a Slab on Grade Supporting Sensitive Equipment -- Experimental Modal Analysis of a Prestressed Concrete Double-tee Joist Roof Subject to Blast -- Structural Evaluation of an Earthen Building from Operational Modal Analysis -- Smart Sensor Nodes for Vibration Measurement of Large Civil Infrastructure -- Floor Vibrations on Healthcare Facilities: A Case Study on a Surgical Microscope -- Modeling Human-structure Interaction Using a Close Loop Control System -- Damage Localisation Using Symbolic Time Series Approach -- Automated Structural Damage Detection Using One-class Machine Learning -- Interaction Between Humans and Structures -- Effects of Human-structure Interaction from Seated Occupants on a Cantilevered Laboratory Test Structure -- Investigating Predicted Floor Response Sensitivity to Input Forcing Function Variables -- Vibration Performance of Bridges Made of Fibre Reinforced Polymer -- Characterization of Human Motion Through Floor Vibrations -- Vision-based Tracking of Human Body Motion -- Mathematical Framework for Real-time Hybrid Substructuring of Marine Structural Systems -- Damage Detection In Civil Engineering Structures Considering Temperature Effect -- Damage Detection on the Z24 Bridge by a Spectral-based Dynamic Identification Technique -- Nonlinear Harmonic Identification of Cracks in Structures -- A Strategy for Improving Performance in Real Time Hybrid Testing -- Development and Performance Analysis of Single Axis Simulation Table for Durability Testing -- Comparative Study of Uncertainty Quantification Metrics via a Stochastic Method of Model Validation -- Structural Identification Using the Applied Element Method: Advantages and Case Study Application -- Identifying Structural Parameters of an Idling Offshore Wind Turbine Using Operational Modal Analysis -- Modal Identification of Golden Gate Bridge Using Pseudo Mobile Sensing Data With STRIDE -- Removing the Influence of Rotor Harmonics for Improved Monitoring of Offshore Wind Turbines -- Evaluating Different Automated Operational Modal Analysis Techniques for the Continuous Monitoring of Offshore Wind Turbines -- Cable Tension Estimation Using Vision-based Monitoring System Under Weather Conditions -- Direct Structural Damping Identification Method -- Modal Analysis and Numerical Models of a Typical Railway Bridge -- Modal and Structural Identification of a Skew, Cable Stayed, Arch Bridge -- A Dynamic Model for Truck-induced Vibrations on a Cable-stayed Bridge -- Numerical Modeling and Dynamic Testing on the Oglio Flyover of the new BreBeMi Highway in Italy -- Comparative Evaluation of Excitation Schemes for Multi-shaker Testing of Bridges -- Ambient Vibration Testing of the Eureka-samoa Channel Bridge -- Ambient Vibration Testing of the Painter St Overpass -- Natural Frequencies of Long-span Suspension Bridges Subjected to Aerodynamic Loads -- Seismic Response Control of Adjacent Buildings Connected by Viscous and Hybrid Dampers -- Comparing Statistical Classification with a Vibro-Tactile Human-Machine Interface for Structural Health Monitoring -- Modal Identification Tests on Archaeological Heritage: The Case of Chokepukio -- Fluid-Structure Interaction Analysis of Vibration Reduction in Pipe Systems -- Application of Positive Position Feedback Control Schemes in a Building-like Structure -- Active Control of Three-dimensional Structures -- Dynamic Vibration Absorber Design for a Motor and Pump Assembly -- Design and Performance Analysis of Inerter-based Vibration Control Systems -- Using Tuned Mass Dampers to Control Imperceptible Motions -- A Simplified Approach for the Dynamic Analysis of High-rise Structures -- A Machine Learning Approach to Nonlinear Modal Analysis.
Keywords: Vibration; Dynamical systems; Dynamics; Mechanical engineering; Mechanics; Mechanics, Applied; Vibration, Dynamical Systems, Control; Mechanical Engineering; Solid Mechanics